Trait stacking via targeted genome editing. Issue 9 (19th August 2013) - Ainley, William M.; Sastry‐Dent, Lakshmi; Welter, Mary E.; Murray, Michael G.; Zeitler, Bryan; Amora, Rainier; Corbin, David R.; Miles, Rebecca R.; Arnold, Nicole L.; Strange, Tonya L.; Simpson, Matthew A.; Cao, Zehui; et al.
Summary Modern agriculture demands crops carrying multiple traits. The current paradigm of randomly integrating and sorting independently segregating transgenes creates severe downstream breeding challenges. A versatile, generally applicable solution is hereby provided: the combination of high‐efficiency targeted genome editing driven by engineered zinc finger nucleases (ZFNs) with modular 'trait landing pads' (TLPs) that allow 'mix‐and‐match', on‐demand transgene integration and trait stacking in crop plants. We illustrate the utility of nuclease‐driven TLP technology by applying it to the stacking of herbicide resistance traits. We first integrated into the maize genome an herbicide resistance gene, pat, flanked with a TLP (ZFN target sites and sequences homologous to incoming DNA) using WHISKERS™‐mediated transformation of embryogenic suspension cultures. We established a method for targeted transgene integration based on microparticle bombardment of immature embryos and used it to deliver a second trait precisely into the TLP via cotransformation with a donor DNA containing a second herbicide resistance gene, aad1, flanked by sequences homologous to the integrated TLP along with a corresponding ZFN expression construct. Remarkably, up to 5% of the embryo‐derived transgenic events integrated the aad1 transgene precisely at the TLP, that is, directly adjacent to the pat transgene. Importantly and consistent with the juxtaposition achieved via nuclease‐driven TLP technology, both herbicide resistance traits cosegregated in subsequent generations, thereby demonstrating linkage of the two independently transformed transgenes. Because ZFN‐mediated targeted transgene integration is becoming applicable across an increasing number of crop species, this work exemplifies a simple, facile and rapid approach to trait stacking.